002.3 Are rapid point-of-care tests for syphilis useful in outbreak settings in remote australia? – an experience from the northern territory. (13th September 2015) - Su, J-Y; Garton, L; Russell, M; Yip, T-W; Gunathilake, M; Thalanany, M; Ryder, N; Krause, V
Abstract : Introduction: A rapid point-of-care test (PoCT) for syphilis was used in two community-wide screens as part of an outbreak response in remote Northern Territory (NT) in 2014. This paper reports the results and evaluation for using PoCT as a tool for outbreak management. Methods: A community-wide screen for people aged 12–30 years was conducted in two remote communities in the NT with high numbers of new cases and contacts, using the OnSite Syphilis Ab Combo Rapid Test. Preparatory work included devising a screening protocol, community engagement, clinical staff training and mobilisation of resources. Results: The two screens were conducted in September to December 2014 in the two communities. The combined population of residents in the targeted age group was 545. A total of 326 individuals (including 57 non-residents) were tested with the PoCT (44.5% males and 55.5% females). The age range was from 12 to 30 years (median: 18, interquartile range: 14–23). Of these, 30 tested positive (13 males and 17 females), giving a combined prevalence among those tested of 9.2% (9.0% in males, 9.4% in females). All positive PoCT results were confirmed positive by normal syphilis serology tests, with 14 and 10 of them categorised as confirmed and probable infectious syphilis cases respectively. Treatment was given on the spot for these cases and contact tracing initiated immediately. Of the 296 tested negative, 5 (1.7%) were found to be false negative later due to past history of infection. Staff reported excellent acceptability of the test method for specimen collection. Conclusion: With prior community engagement, updated population lists, screening protocols, and staff training, using PoCT for syphilis can be an effective for case detection in an outbreak setting in remote Indigenous communities in Australia. However, given the reported sensitivity of the PoCT used, retesting in 3 months is important. Disclosure of interest statement: No potential conflicts of interest are identified.